O/W emulsions stabilized by interactions between proteins and polysaccharides - Nicoletti Telis, Vânia Regina [UNESP] (Elsevier, 2018)
Amphiphilic structures can be produced from interactions between proteins and polysaccharides, resulting in supramolecular microstructures very suitable to replace synthetic emulsifiers. These association colloids may be formed by electrostatic interactions or covalent bonding, and both will benefit from the complementary properties of proteins and polysaccharides, which combine the emulsifying activity of proteins with the polysaccharide ability of interacting with the proteins and stabilizing O/W emulsions. The protein-polysaccharide complexes do not require special legislation and are being increasingly used to improve food stabilization, enhancement of textural properties and creation of reduced-fat food systems, microencapsulation of bioactive compounds, as well as other potential applications. This article presents some fundamental concepts involved in the functionality of protein-polysaccharide interactions as emulsifying and stabilizing elements in O/W emulsions.
Keywords: Adsorption; Amphiphilic structure; Covalent bonding; Dispersed system; Electrostatic interaction; Emulsifier; Interfacial activity; Polysaccharide; Protein; Stabilizer; Supramolecular structure; Surface charge